Efektivitas PPT Interaktif Dalam Pembelajaran Matematika Kelas V di SD N 6 Dauhwaru - A.A. Bagus Tri Rama Antara; Edi Waluyo; Deni Setiawan (LPPM Politeknik Pratama, 2023)
Learning mathematics is a subject that prohibits thinking logically, systemati-cally, and rationally, so that this subject is important for students to learn. However, the facts show that there are still many students who are not interested in mathematics, so they have difficulty understanding the material. In the learning process, class teachers only rely on conventional methods in the learning process of mathematics and do not maximize the use of learning media, especially those based on technology, so there is a need for a touch of innova-tion in the application of learning media to learning mathematics. This study aims to determine the effectiveness of interactive PPT media when applied to a school that can be classified as being in a rural area with minimal use of tech-nology in the learning process. This study uses a descriptive quantitative method by taking all actions on the object of research. The method of data analysis was carried out by carrying out several test stages, namely the classical assumption test and the one sample t test using a test tool in the form of SPSS version 22. The study was conducted on all 31 students of class V, totaling 31 students. The data collection instrument used was a test related to fractional material. Based on the results of the research and discussion of the research, it can be concluded that in-active PPT media is effective to be applied in learning mathematics, especially in fraction material at SD N 6 Dauhwaru.